Letter to Jane Tolmach from Jerry Whipple, Director of UAW Region 6 - Jerry Whipple:::::: (1976)
This June 9, 1976 mailgram from Jerry Whipple, Director of UAW Region 6, congratulates Jane Tolmach on her primary election victory. On behalf of the UAW Region 6 Community Action Program Council, he extended best wishes for success in the upcoming general election.